2015
DOI: 10.3390/f6062109
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Ecosystem Development on Different Site Types in Reclaimed Boreal Forests

Abstract: Forest development after land reclamation in the oil sands mining region of northern Alberta, Canada was assessed using long-term monitoring plots from both reclaimed and natural forests. The metrics of ecosystem development analyzed included measures of plant community structure and composition and soil nutrient availability. Early seral reclamation plots were grouped by site type (dry and moist-rich) and age categories, and these were compared with mature natural forests. There were few significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
49
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 30 publications
11
49
3
Order By: Relevance
“…Given that a greater proportion of the upland is under FFM cover substrate, these invasive forbs and grasses were the dominant vegetation cover throughout the upland. Similar results were observed in an upland reclamation study, which confirmed that non‐native forbs and grasses dominate reclaimed uplands for the first 5 years post soil placement but gradually decline with development of a canopy cover by planted saplings (B. Pinno & Hawkes, ).…”
Section: Discussionsupporting
confidence: 80%
“…Given that a greater proportion of the upland is under FFM cover substrate, these invasive forbs and grasses were the dominant vegetation cover throughout the upland. Similar results were observed in an upland reclamation study, which confirmed that non‐native forbs and grasses dominate reclaimed uplands for the first 5 years post soil placement but gradually decline with development of a canopy cover by planted saplings (B. Pinno & Hawkes, ).…”
Section: Discussionsupporting
confidence: 80%
“…() and Pinno and Hawkes (). This probably resulted from reduced resource availability in the understorey with increasing overstorey canopy closure and standing biomass as stands age from stand initiation stage to stem exclusion stage (Audet et al., ; Bartels & Chen, ; Chen & Popadiouk, ; Halpern & Lutz, ; Pinno & Hawkes, ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Using stratified random sampling, we sampled a total of 94 reclaimed sites with known reclamation history (Table ). These sites were part of the Cumulative Environment Management Association (CEMA)'s Long Term Plot Network, which was established in 2000 to monitor long‐term changes in vegetation and soils following oil sands mining and reclamation (Pinno & Hawkes, ). To determine the effects of substrate type, we selected sites that were reclaimed with three different substrate materials: overburden, secondary overburden and tailings sand.…”
Section: Methodsmentioning
confidence: 99%
“…This approach, largely adopted from the forest industry, maximizes individual tree growing space and growth but results in very open stands with little intraspecific competition among trees and a greatly delayed time to reach crown closure, up to 30 years or more in many cases. Reclamation sites can also experience very intense weed pressure from undesirable non-native species (Sloan and Jacobs, 2013;Pinno and Hawkes, 2015). These undesirable species can persist until canopy development reduces light availability to a point that these shade intolerant early successional species fall out of the stand, which can take decades in widely spaced stands.…”
Section: Introductionmentioning
confidence: 99%